Introducing bimetallic MOF-based electrochemical sensor for voltametric nanogram determination of sulfadimidine: various applications and a comprehensive sustainability assessment - Hind A. Abdullatif; Mohammed Abdelkawy; Shereen A. Boltia; Nesma M. Fahmy; Maha Kamal (BMC Chemistry)
Abstract Due to its characteristics and allowable use, the sulphonamide group remains a first-choice treatment for veterinarians when managing multiple veterinary diseases. Unfortunately, long-term consumption of food containing sulphonamide residues can result in harmful effects, especially that sulphonamides are classified in category D. Metal–organic frameworks (MOFs) have demonstrated outstanding selectivity in detecting target components due to their large surface areas and intricate structures. In this study, we present a novel voltammetric approach for determining sulfadimidine (SLD) in veterinary formulations, animal plasma, and animal-derived products, including milk and eggs. We employed a bimetallic Cu/Ni-MOF to modify a carbon paste electrode, utilizing differential pulse voltammetry (DPV) for SLD detection. The morphology of the Cu/Ni-MOF was analyzed to ensure optimal structural characteristics, and experimental conditions were optimized to achieve the best performance. A major advantage of this method is its wide linearity range (100 nM to 100,000 nM) and the ability to detect SLD at nanogram levels, with a LOD of 20 nM and a LOQ of 60 nM. These characteristics demonstrate the fabricated Cu/Ni-MOF’s capability to detect SLD at levels below its maximum residue limit (MRL) in plasma, milk, and eggs. Furthermore, the environmental impact of this method was assessed using the RGB 12 metric and compared against the AGREE, Complex GAPI, and BAGI metrics, offering a comprehensive evaluation of its analytical performance and practical advantages. This approach holds promise for curbing antibiotic misuse by providing a straightforward and effective method for SLD detection across multiple matrices.